Body mass index as a determinant of clozapine plasma concentrations: A pharmacokinetic-based hypothesis. (March 2021) - Kuzin, Maxim; Haen, Ekkehard; Hiemke, Christoph; Bochon, Benjamin; Bochon, Karolina; Gründer, Gerhard; Paulzen, Michael; Schoretsanitis, Georgios
Background: Knowledge regarding the impact of body composition measures on pharmacokinetics of antipsychotics is limited. Aims: Our aim was to investigate the impact of body weight and body mass index on clozapine pharmacokinetics using a therapeutic drug monitoring database. Methods: A large therapeutic drug monitoring dataset of clozapine plasma concentrations considering three patient subgroups was analysed: a control group (CLZ0, 20–30 kg/m 2, n =266), a group with high body mass index (CLZhigh, body mass index ⩾30 kg/m 2, n =162) and with low body mass index values (CLZlow, body mass index <20 kg/m 2, n =27). Comparisons of plasma and dose-adjusted plasma concentrations (C/D) of clozapine were based on the Spearman's correlation ( r s), Kruskal Wallis and Mann-Whitney-U tests. For percentages we used the Pearson chi-square test (χ 2 ). To assess effects of confounders we used bootstrapping analysis of covariates. Results/outcomes: Regarding demographic characteristics, groups differed only for sex percentage with more females than males in CLZlow and CLZhigh compared to CLZ0 ( p =0.001 for χ 2 test). Plasma and C/D values were positively associated with body mass index ( r s=0.108, p =0.022 and r s=0.156, p =0.001 respectively). Intergroup differences were observed for plasma and dose-adjusted concentrations of clozapine ( p =0.031 and p =0.029 for Kruskal Wallis respectively): post-hoc pairwise comparisons showed higher plasma concentrations and C/D of clozapine in CLZhigh compared to CLZ0 ( p =0.014 and p =0.007 respectively for Mann-Whitney U-test), by mean 21 and 18%, respectively. Differences for C/D values remained after accounting for sex ( p =0.02). Conclusions/interpretation: In obese patients, bioavailability, distribution or elimination of clozapine may be altered due to increased clozapine deposits in fat tissue and hepatic enzyme activity changes.